Message reception analysis on K to 12 curriculum as encoded on May 2012 training for teachers in Panabo City Division of Department of Education - Godoy, Agnes M.
Last June of 2012, the Department of Education had rolled out the K to 12 Basic Education Program in all public schools in the country. It revolutionized the basic education system of the Republic of the Philippines by instituting a new curriculum and by changing its structure. This move had made the country on with the rest of the Asian nations, and of the whole world, in utilizing the same curriculum. Since the introduction of the new curriculum entailed preparedness, the Central Office called for a mass training for teachers a month prior to its roll out. Since the primary concern of trainings had been to affect positive attitude on the employee toward the job being communicated, this paper had looked into the reception of the Grade 1 teachers in Panabo City Division of DepEd on the K to 12 Curriculum. After conducting a survey using a questionnaire that was formatted after the diamond of opposites scaling methods and after conducting interviews, this study revealed that the positiveness of the Grade 1 teachers in the three focal schools outweighed their negativeness toward the K to 12 Curriculum. It could be said that the interpersonal communication process that had transpired during the training had been successful. However, these teachers had not been 100% positively affected by it. This aspect of the result also suggested something about the communication process. It was revealed that trainers and quality of messages were the contributing factors of this result.